2011
DOI: 10.3758/s13414-011-0236-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal shapes of sound markers on the perception of interonset time intervals

Abstract: This study investigated how the temporal characteristics, particularly durations, of sounds affect the perceived duration of very short interonset time intervals (120-360 ms), which is important for rhythm perception in speech and music. In four experiments, the subjective duration of single time intervals marked by two sounds was measured utilizing the method of adjustment, while the markers' durations, amplitude difference (which accompanied the duration change), and sound energy distribution in time were va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(84 reference statements)
2
14
0
Order By: Relevance
“…The data showed that listeners instead matched the onset-to-onset durations of the two stimuli, rather than basing judgments on actual gap durations. Hasuo, Nakajima, Osawa, and Fujishima (2011) reported the results of experiments designed to study the perception of rhythm, or onset-to-onset times, in marker-gap-marker stimuli. Hasuo et al instructed listeners to match the onsetto-onset durations of marker-gap-marker stimuli in which the markers were 1-kHz pure-tone bursts, using a method of adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed that listeners instead matched the onset-to-onset durations of the two stimuli, rather than basing judgments on actual gap durations. Hasuo, Nakajima, Osawa, and Fujishima (2011) reported the results of experiments designed to study the perception of rhythm, or onset-to-onset times, in marker-gap-marker stimuli. Hasuo et al instructed listeners to match the onsetto-onset durations of marker-gap-marker stimuli in which the markers were 1-kHz pure-tone bursts, using a method of adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…This is an example of possible devices for the adjustment method. Indeed, various types of devices have been used in previous studies [12,17,18].…”
Section: Understanding Of the Methodsmentioning
confidence: 99%
“…Some physical properties of sounds, such as frequency or spatial location, can affect the perceived duration of the intervals delimited by these sounds [5][6][7][8][9]. For example, an interval between two sounds' onsets is perceived as longer when each sound lasts longer, even if this interval is physically fixed at a constant duration [10][11][12] 1 . Such factors can also affect listeners' ability of discriminating two intervals; listeners à e-mail: tkuroda@neurophy.med.kyushu-u.ac.jp 1 Strictly speaking, empty time intervals are classified into two categories: One, called the inter-onset interval (or stimulus onset asynchrony), is delimited by the onsets of two stimuli, while the other, called the inter-stimulus interval, is delimited by the termination of the preceding stimulus and the onset of the following stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The present study focused on the accuracy issue; in other words, we investigated the effects of sound length on the perceived duration of empty intervals. Woodrow (1928) and Hasuo et al (2012) examined how the perceived duration of single empty intervals, marked by two successive sounds, is modulated by the lengthening of each sound. Woodrow fixed an interstimulus (offset to onset) interval between two sounds at 500 ms and found that this Electronic supplementary material The online version of this article (doi:10.3758/s13414-016-1172-x) contains supplementary material, which is available to authorized users.…”
mentioning
confidence: 99%
“…Some of these studies focus on the length of sounds marking empty intervals, examining one of the following issues: (1) how the listener's ability for detecting a change in the duration of empty intervals, as expressed by the just-noticeable difference or the slope of psychometric functions, is modulated by the lengthening of each marker (Grondin, Roussel, Gamache, Roy, & Ouellet, 2005;Grose, Hall, & Buss, 2001;Kuroda, Hasuo, & Grondin, 2013;Penner, 1976;Rammsayer & Leutner, 1996), and (2) how the perceived duration of empty intervals, as expressed by a point of subjective equality, is modulated by the lengthening of each marker (Hasuo, Nakajima, Osawa, & Fujishima, 2012;Woodrow, 1928). The former issue is concerned with the sensitivity (or variability) of the timekeeping process, and the latter one with its accuracy.…”
mentioning
confidence: 99%